Measurement of Anti-Corruption Literacy Index (ALI) & amp for the Young Generation Based on Perception, Participation - Suriadi, Jadi (University of Darussalam Gontor Press, 2022)
The study is emprical case of Young Generation Anti-Corruption Literacy Index (ALI). it was conducted with a scope of students from SMKN1 Gambut, Banjar, South Kalimantan. The number of registered students is 908, for various reasons it is estimated that only about 900 have reached as the target. The number of responsed collected was 724 or a “response rate” is 80.05%. Answering the question how is the ALI measurement carried out? Researcher describe: 1). By using the wellbeing methodology (WM) approach; 2). Designing object, defining sub-objects (variables) with expert group discussion (EGD); 3). Carry out sociometric measurements and design online e-survey instruments and cloud computing. The measurement includes an assessment based on the perspective of perception, participation and acceptability (PPA) on each variable, using a purposive population. The results of these measurements are then accumulated in the form of an index. This index is a kind of composite index. The value score is a numeric number from a scale of 9, no conversion is carried out, calculated accumulatively, all scores are tested for significance. The significance reference standard (SRS) was used. From the data presented, it can be seen that all scores show a much higher value than the SRS score. This means that the results of ALI for students at SMKN1 Gambut, Banjar are significant. From the comparison of scores, the highest value is on the X5 variable, namely